The Correlation Of Insomnia And Anxiety In Students Of The Faculty Of Medicine, University Of Pelita Harapan - Kinley Dhinata; Nicolaski Lumbuun (Medicinus, 2022)
Background and Aim: Insomnia and anxiety are common disorders with a high prevalence rate, especially in medical students. Moreover, many confounding factors play a role in influencing anxiety. Most studies do not include or measure other confounding factors of anxiety in the analysis. This requires research that examines insomnia and anxiety assessing the contribution of the factors influencing anxiety.Methods: A cross-sectional study methodology with linear regression analysis on a sample of students from the Faculty of Medicine, University of Pelita Harapan using the DASS-21 questionnaire to assess anxiety and ISI to assess insomnia.Results: Prevalence rates of insomnia was 34.29% and anxiety 32.38% in Pelita Harapan University medical student. From the results of the bivariate linear regression, a weak relationship between insomnia and anxiety (r = 0.322; p = 0.000) is seen. In multivariate results, there were confounding stress variables (r = 0.565; p = 0.000) and trauma (r = 0.250; p = 0.005) which contributed greatly to anxiety (In order of largest).Conclusion: There is a weak correlation and anxiety. Moreover, the high prevalence rate of anxiety in medical students may be contributed heavily not only by insomnia but also by stress and childhood trauma.